Structural changes and band gap tailoring on α-MoO3 by exfoliation techniques. (2022) - Manuja, M.; Thomas, Tintu; Jose, Joshy; Jose, Gijo
Abstract: Layered α-MoO3 is prepared via the hydrothermal procedure and a facile exfoliation technique is followed to cut down the number of layers. The polyhedral structure is obtained from Rietveld refinement procedure and the importance of van der Waals interaction in formation of layered nature is identified. The absence of (0 10 0) peak in the exfoliated x-ray diffraction profiles, and diminishing of the characteristic peak of lamellar α-MoO3 (at 486.4 cm −1 ) in exfoliated Raman spectra indicates the suppression of layered nature along the b axis. The bandgap widening (3.6–4.1 eV) obtained from tauc plots also confirms the effect of exfoliation in the material.